PENGARUH PARAMETER JARINGAN, KONDISI OPERASI DAN STRUKTUR JARINGAN PADA MODE PERTUKARAN ENERGI DOMINAN ANTAR WILAYAH, MENGGUNAKAN METODE PENDEKATAN ENERGI - Nainggolan, Benhur
Interarea oscillation is one problem which get attentions from obserbers. On the previous observation by C.Jing , et all used energy function method to analyze this matter. This oscillation is characterized as oscillatory behavior, following a disturbance, of the rotor motion for two or more generator groups such that there is aperiodic interchange of energy between them. By comparing the phase of the coefficient of dominant kinetic energy for each generator we identify the groups for which there are periodic interchange of energy. The location of these groups in the system provides the information about the transmission line over which the energy interchange is taking plase. These thesis is talking about the kind of parameters which influence the dominant interarea energy mode (DIEMs) between generator. The evaluations by ETAP version 7.35 and computation by MATL,AB version 4.1, can identify in the result that resistance and capacitance parameters influence the changing of energy accured both in local area or interarea.